IMMUNOLOGICAL PARAMETERS AND OXYPROLINE METABOLISM IN SUBJECTS WITH CARDIAC CONNECTIVE TISSUEDYSPLASIAS AND AUTONOMIC DYSFUNCTION - M P Smirnova; Petr Aleksandrovich Chizhov; A A Baranov; V V Tabakov; M A Gurmach; M P Smirnova; Petr Aleksandrovich Chizhov; A A Baranov; V. V. Tabakov; M A Gurmach (Научно-практическая ревматология, 2010)
The blood levels of native DNA antibodies, rheumatoid factor, IgG and IgM cardiolipin antibodies, and free and protein-bound oxyproline were compared in subjects with and without various cardiac dysplasias in the presence and absence of autonomic dysfunction. There were differences in these parameters between the study groups.